Optimal operation of a hydrogen refuelling station combined with wind power in the electricity market. (14th December 2016) - Carr, Stephen; Zhang, Fan; Liu, Feng; Du, Zhaolong; Maddy, Jon
Abstract: An optimisation routine has been developed to analyse the performance of hydrogen refuelling stations combined with wind power operating in electricity markets. This optimisation routine includes the minimum turn down ratio of the electrolyser in its formulation resulting in a mixed integer nonlinear programming optimisation. The optimisation routine has been used to analyse the performance of a hydrogen refuelling station located at the advanced manufacturing park in Rotherham, UK. The performance of the optimisation routine for various scenarios of hydrogen demand and wind power has been assessed. This includes the effect of operating the electrolyser to reduce wind curtailment in a grid constrained scenario. It is found that the optimisation routine is capable of increasing profits when operating in the market, but this is dependent on various factors such as the level of hydrogen demand and wind power. Highlights: An optimization routine for operation of a hydrogen refuelling station is proposed. The routine optimizes operation in the electricity market. The optimization routine is used to simulate operation of a refuelling station. The optimization routine significantly improves performance.